Aluminum alloy foil for battery packaging material, battery packaging material, and battery

By optimizing the crystal structure and grain size of aluminum alloy foils, the challenges of pinhole and crack formation in battery packaging materials are addressed, resulting in enhanced moldability and improved battery performance.

JP7658417B2Active Publication Date: 2025-04-08DAI NIPPON PRINTING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023221456
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-12-28
Filing Date
2023-12-27
Publication Date
2025-04-08
Estimated Expiration
2037-12-27

AI Technical Summary

Technical Problem

Conventional aluminum alloy foils with small average grain sizes used in battery packaging materials are prone to pinholes and cracks, compromising their moldability and ability to meet the demands of diverse battery shapes, thinness, and weight reduction.

Method used

The development of an aluminum alloy foil with a specific crystal structure, where the {111} plane occupies 10% or more of the total crystal surface area and the number average grain size is related to the foil thickness by the formula R≦0.056X+2.0, enhancing moldability and reducing the likelihood of pinholes and cracks.

Benefits of technology

This solution achieves excellent moldability and reduces the occurrence of pinholes and cracks in aluminum alloy foils used in battery packaging materials, even when the foils are thin, thereby supporting the production of batteries with diverse shapes and improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658417000006
    Figure 0007658417000006
  • Figure 0007658417000007
    Figure 0007658417000007
  • Figure 0007658417000008
    Figure 0007658417000008
Patent Text Reader

Abstract

To provide an aluminum alloy foil that, when used for battery packaging material, is unlikely to develop pinholes or cracks even during molding of the battery packaging material, and can exhibit excellent moldability.SOLUTION: There is provided an aluminum alloy foil 1 for use in battery packaging material. In the aluminum alloy foil, with respect to cross section obtained by cutting the aluminum alloy foil in a vertical direction to a rolling direction of the aluminum alloy foil, which is a vertical direction to a surface of the aluminum alloy foil, proportion of total area of a {111} plane in total area of crystal planes of a face-centered cubic lattice structure, obtained by performing crystal analysis using an EBSD method, is 10% or more; and with respect to the cross section, a number average grain diameter R (μm) of crystals in a face-centered cubic lattice structure, obtained by performing crystal analysis using an EBSD method, satisfies the following equation. Number average grain diameter R≤0.056X+2.0, where X=thickness (μm) of the aluminum alloy foil.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy foil for use as a packaging material for batteries, a packaging material for batteries, and a battery. [Background technology]

[0002] Conventionally, various types of batteries have been developed. In these batteries, the battery elements composed of electrodes, electrolytes, etc. need to be sealed with packaging materials, etc. Metal packaging materials are widely used as packaging materials for batteries.

[0003] In recent years, batteries with various shapes are required due to the high performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc. In addition, batteries are also required to be thin and lightweight. However, it is difficult for the conventionally widely used metal packaging materials to keep up with the diversification of battery shapes. In addition, since the packaging materials are made of metal, there is a limit to how much the packaging materials can be made lighter.

[0004] Therefore, a film-like battery packaging material in which a base material layer, an aluminum alloy foil, and a heat-sealable resin layer are laminated in that order has been proposed as a battery packaging material that can be easily processed into a variety of shapes and can be made thin and lightweight.

[0005] In such a film-like battery packaging material, recesses are generally formed by cold forming, and battery elements such as electrodes and electrolyte are placed in the space formed by the recesses. The heat-sealable resin layers are then heat-sealed to each other to obtain a battery in which the battery elements are housed inside the battery packaging material.

[0006] However, such battery packaging materials are thinner than metallic packaging materials and have the disadvantage that pinholes and cracks are easily generated during molding.

[0007] As an aluminum alloy foil with improved formability, for example, Patent Document 1 discloses an aluminum alloy soft foil having a composition containing, by mass%, 1.4% to 2.0% Fe, 0.15% or less Si, with the balance being Al and unavoidable impurities, an average crystal grain size of 5 μm or less, and a maximum crystal grain size / average crystal grain size ratio of 3.5 or less. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2015-203154 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present inventors have found that when an aluminum alloy foil having a small average crystal grain size is used for a battery packaging material, such as a conventional aluminum alloy foil disclosed in Patent Document 1, the formability is evaluated and the aluminum alloy foil may not exhibit the high formability required in recent years, resulting in pinholes, cracks, etc. In other words, it has become clear that the high formability required in recent years for battery packaging materials cannot be fully exhibited by simply using an aluminum alloy foil having a small average crystal grain size.

[0010] The present invention has been made in consideration of such problems in the prior art. That is, the main object of the present invention is to provide an aluminum alloy foil that, when used in a battery packaging material, is unlikely to cause pinholes or cracks even when the battery packaging material is molded, and can exhibit excellent moldability. Another object of the present invention is to provide a battery packaging material using the aluminum alloy foil, and a battery using the battery packaging material. [Means for solving the problem]

[0011] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, it has been found that an aluminum alloy foil in which the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure obtained by performing crystal analysis by EBSD on a cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is 10% or more, and the number average crystal grain size R (μm) of the crystals of the face-centered cubic lattice structure obtained by performing crystal analysis by EBSD on the cross section satisfies the following formula, is used as a battery packaging material, and pinholes and cracks are unlikely to occur during molding of the battery packaging material, and excellent formability can be exhibited. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

[0012] That is, the inventors have found that the formability is not improved by simply reducing the average crystal grain size of the aluminum alloy foil, but that excellent formability is exhibited when used as a battery packaging material when a ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure obtained by performing crystal analysis by EBSD method on aluminum crystal faces aligned parallel to a cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil from the surface of the aluminum alloy foil is 10% or more, and further, when the number average crystal grain size of the crystals of the face-centered cubic lattice structure obtained from the cross section has a specific relationship with the thickness of the aluminum alloy foil.

[0013] In addition, regarding the cross section, the {111} plane aligned parallel to the cross section is <111> / / is synonymous with RD, where <111> / / RD is an aluminum alloy foil containing a face-centered cubic (FCC) structure. <111> It means that the orientation is parallel to the rolling direction (RD).

[0014] The present invention was completed based on these findings and through further investigation.

[0015] That is, the present invention provides the following aspects. Item 1. An aluminum alloy foil for use as a packaging material for batteries, A cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is subjected to crystal analysis using an EBSD method, and the ratio of the total area of ​​{111} planes to the total area of ​​crystal planes of a face-centered cubic lattice structure is 10% or more; and The aluminum alloy foil for battery packaging material has a number average crystal grain size R (μm) of crystals having a face-centered cubic lattice structure, which is obtained by performing crystal analysis on the cross section using the EBSD method, and satisfies the following formula. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm) Item 2. The aluminum alloy foil for battery packaging material according to Item 1, wherein the ratio (%) of the total area of ​​{111} faces to the total area of ​​the crystal faces of the face-centered cubic lattice structure satisfies the following formula: The ratio (%) of the total area of ​​{111} faces to the total area of ​​the crystal faces of the face-centered cubic lattice structure is ≧ -1.1X+66 X = thickness of the aluminum alloy foil (μm) Item 3. The aluminum alloy foil for battery packaging material according to Item 1 or 2, wherein the standard deviation St of the crystal grain size satisfies the following formula: Standard deviation of grain size St≦0.09X+0.5 X = thickness of the aluminum alloy foil (μm) Item 4. The aluminum alloy foil for battery packaging material according to any one of Items 1 to 3, which contains iron. Item 5. The aluminum alloy foil for battery packaging material according to any one of Items 1 to 4, wherein a surface of the aluminum alloy foil is provided with an acid-resistant coating containing at least one element selected from the group consisting of phosphorus, chromium, and cerium. Item 6. The aluminum alloy foil has an acid-resistant coating on its surface, When the acid-resistant film was analyzed using time-of-flight secondary ion mass spectrometry, Ce + and Cr + 5. The aluminum alloy foil for battery packaging material according to any one of items 1 to 4, wherein a peak derived from at least one of the following is detected. Item 7. The aluminum alloy foil for battery packaging material according to any one of Items 1 to 4, wherein the surface of the aluminum alloy foil is provided with an acid-resistant coating film containing at least one selected from the group consisting of phosphorus compound salts, chromium compounds, fluorine compounds, and triazine thiol compounds. Item 8. The aluminum alloy foil for use as a battery packaging material according to any one of Items 1 to 4, wherein the aluminum alloy foil has a surface provided with an acid-resistant coating film containing a cerium compound. Item 9. A packaging material for batteries, comprising a laminate including at least a base layer, the aluminum alloy foil for battery packaging material according to any one of Items 1 to 8, and a heat-sealable resin layer, in this order. Item 10. A battery, comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the battery packaging material according to item 9. Effect of the Invention

[0016] According to the present invention, it is possible to provide an aluminum alloy foil that is used in a battery packaging material and is unlikely to cause pinholes or cracks during molding of the battery packaging material, thereby exhibiting excellent formability. Furthermore, according to the present invention, it is also possible to provide a battery packaging material using the aluminum alloy foil, and a battery using the battery packaging material. [Brief description of the drawings]

[0017] [Figure 1] 1A is a schematic diagram of an aluminum alloy foil according to the present invention, and FIG. 1B is a schematic diagram of a battery packaging material. [Diagram 2] This is a photograph (magnification 100x) obtained by observing the glossy surface of a commercially available aluminum alloy foil (Sunfoil manufactured by Toyo Aluminum Co., Ltd.) with a metallurgical microscope. [Diagram 3]1 is a schematic diagram of crystal planes of a face-centered cubic lattice structure in a cross section obtained by cutting the aluminum alloy foil according to the present invention in a direction perpendicular to the rolling direction from the surface of the aluminum alloy foil, in which the colored regions indicate {111} planes. [Figure 4] FIG. 1 is a schematic cross-sectional view of an example of a battery packaging material according to the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view of an example of a battery packaging material according to the present invention. [Figure 6] FIG. 1 is a schematic cross-sectional view of an example of a battery packaging material according to the present invention. [Figure 7] FIG. 1 is a schematic cross-sectional view of an example of a battery packaging material according to the present invention. [Figure 8] 1 is a graph showing the relationship between the thickness X (μm) of an aluminum alloy foil and the ratio (%) of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure in Examples and Comparative Examples. [Figure 9] 1 is a graph showing the relationship between the thickness X (μm) of the aluminum alloy foil and the number average crystal grain size (μm) in the examples and comparative examples. [Figure 10] 1 is a graph showing the relationship between the thickness X (μm) of an aluminum alloy foil and the standard deviation of the crystal grain size in Examples and Comparative Examples. [Figure 11] 1 is a graph showing the relationship between the thickness X (μm) of the aluminum alloy foil and the limit forming depth (μm) in Examples and Comparative Examples. [Figure 12] FIG. 2 is a schematic diagram for explaining a method of performing crystal analysis by the EBSD method on a cross section of an aluminum alloy foil. [Figure 13] FIG. 2 is a schematic diagram (two-dimensional) for explaining a method for performing crystal analysis by the EBSD method on a cross section of an aluminum alloy foil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The aluminum alloy foil of the present invention is used for a packaging material for batteries. The aluminum alloy foil is characterized in that the ratio of the total area of ​​{111} planes to the total area of ​​crystal faces of a face-centered cubic lattice structure obtained by performing crystal analysis by EBSD on a cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil (hereinafter, "the ratio of the total area of ​​{111} planes to the total area of ​​crystal faces of a face-centered cubic lattice structure" may be abbreviated as "the ratio of the total area of ​​{111} planes") is 10% or more, and the number average crystal grain size R (μm) of the crystals of the face-centered cubic lattice structure obtained by performing crystal analysis by EBSD on the cross section satisfies the following formula: Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

[0019] The aluminum alloy foil of the present invention, the battery packaging material using the aluminum alloy foil, and the battery using the battery packaging material will be described in detail below with reference to Figs.

[0020] In the present invention, the EBSD (Electron Backscattered Diffraction Pattern: EBSD) method is a method using an EBSD detector, which is one of the detectors mounted on a scanning electron microscope (SEM), and is a method for measuring the fine crystal orientation of a crystal sample by capturing and analyzing the Kikuchi pattern derived by electron backscatter diffraction on an EBSD detector screen. In addition, in this specification, a numerical range indicated by "to" means "more than or equal to" or "less than or equal to". For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.

[0021] 1. Aluminum alloy foil The aluminum alloy foil 1 of the present invention is used for a packaging material for batteries. Specifically, the aluminum alloy foil of the present invention is used for a film-like packaging material for batteries composed of a laminate, and in addition to improving the strength of the packaging material for batteries, it functions as a barrier layer for preventing the intrusion of water vapor, oxygen, light, etc. into the inside of the battery. Specific examples of packaging materials for batteries using the aluminum alloy foil of the present invention will be described later.

[0022] In the present invention, the ratio of the total area of ​​{111} planes to the total area of ​​crystal planes of the face-centered cubic lattice structure obtained by performing crystal analysis by EBSD method on a cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil from the surface of the aluminum alloy foil is 10% or more. Here, the rolling direction of the aluminum alloy foil 1 corresponds to the RD when the aluminum alloy foil is manufactured through a rolling process. In the rolling direction (RD) of the aluminum alloy foil 1, linear lines called so-called rolling marks are formed on the surface of the aluminum alloy foil 1 as shown in the schematic diagram of FIG. 1(a). Since the rolling marks extend along the rolling direction, the rolling direction of the aluminum alloy foil 1 can be grasped by observing the surface of the aluminum alloy foil 1. In the schematic diagram of FIG. 1, RD stands for Rolling Direction, TD stands for Transverse Direction, ND stands for Normal Direction, and MD stands for Machine Direction, respectively. For reference, FIG. 1(b) also shows a schematic diagram of a battery packaging material 10 (for example, an aluminum alloy foil 1 having a base layer 2 on one side and a heat-sealable resin layer 3 on the other side). The RD of the aluminum alloy foil 1 shown in FIG. 1(a) corresponds to the MD of the battery packaging material 10 shown in FIG. 1(b). The TD of the aluminum alloy foil 1 shown in FIG. 1(a) corresponds to the TD of the battery packaging material 10 shown in FIG. 1(b). Furthermore, for reference, FIG. 2 shows a photograph (magnification 100 times) obtained by observing the glossy surface of a commercially available aluminum alloy foil (Sunfoil manufactured by Toyo Aluminum Co., Ltd.) with a metallurgical microscope. In the photograph of FIG. 2, the black linear streaks are rolling marks T, and it can be seen that the rolling marks T extend in the rolling direction (RD). The rolling marks on the surface of the aluminum alloy foil can also be confirmed using a device other than a metallurgical microscope (such as an optical microscope) as long as the device can observe the surface at a magnification of about 50 to 100 times.

[0023] The aluminum alloy foil of the present invention contains aluminum crystals having a face-centered cubic lattice structure, and in the present invention, the crystal orientation of the aluminum crystals is analyzed by EBSD method, focusing on the {111} plane of the face-centered cubic lattice structure of the aluminum crystals. As described later, the aluminum alloy foil of the present invention is preferably composed of about 90 mass% or more of aluminum, but depending on the composition of other components, it may further contain aluminum crystals other than the face-centered cubic lattice structure.

[0024] The fact that the aluminum alloy foil contains aluminum crystals having a face-centered cubic lattice structure can be easily estimated from the Kikuchi pattern obtained by analyzing the aluminum alloy foil by the EBSD method. Furthermore, in order to accurately measure whether the aluminum alloy foil contains aluminum crystals having a face-centered cubic lattice structure, one of the following two methods is carried out. If the surface of the aluminum alloy foil is exposed, it can be structurally analyzed using an X-ray diffraction device. If the aluminum alloy foil is covered with a resin or the like and the surface of the aluminum alloy foil is not exposed, first, a slice sample of the aluminum alloy foil having a thickness of about 100 nm or less is prepared by polishing, a microtome, a focused ion beam, a broad ion beam, or the like. Next, the slice sample can be structurally analyzed by obtaining and analyzing a selected area diffraction pattern of a transmission electron microscope.

[0025] 3 is a schematic diagram of the crystal planes of the face-centered cubic lattice structure in the cross section of the aluminum alloy foil according to the present invention, in which the colored areas indicate the {111} planes.

[0026] From the viewpoint of more effectively improving the formability of the aluminum alloy foil of the present invention, the ratio of the total area of ​​the {111} plane is preferably about 20% or more, more preferably about 30% or more, even more preferably about 40% or more, and particularly preferably about 50% or more. In the aluminum alloy foil, the {111} plane serves as a slip surface during forming, so that the aluminum alloy crystals become more easily slippery as the ratio of the total area in the plane direction increases, and formability is improved. The ratio of the total area of ​​the {111} plane means the ratio of the total area of ​​the {111} plane to the total area of ​​the crystal planes of the face-centered cubic lattice structure arranged parallel to the above-mentioned cross section. However, when the measurement sample is placed on the sample stage, an error may occur in the installation position, so "parallel to the cross section" may include an error of about 10°.

[0027] The upper limit of the total area ratio of the {111} faces is not particularly limited and may be about 100%, but since there is a concern that the extensibility in a specific direction may be specialized and moldability may be reduced, the upper limit may be, for example, about 90% or about 80%, and the lower limit may be, for example, about 25% or more or about 29% or more. Preferred ranges of the total area ratio of the {111} faces include about 10 to 90%, about 10 to 80%, about 20 to 90%, about 20 to 80%, about 25 to 90%, about 25 to 80%, about 29 to 90%, about 29 to 80%, about 30 to 90%, about 30 to 80%, about 40 to 90%, about 40 to 80%, about 50 to 90%, and about 50 to 80%.

[0028] In the present invention, from the viewpoint of more effectively enhancing the formability of the aluminum alloy foil, it is preferable that the ratio (%) of the total area of ​​the {111} faces satisfies the following formula: Percentage of the total area of ​​{111} faces (%) ≧-1.1X+66 X = thickness of the aluminum alloy foil (μm)

[0029] That is, when the thickness of the aluminum alloy foil is small, it is desirable that the ratio of the total area of ​​the {111} faces is large. As the thickness of the aluminum alloy foil becomes smaller, the influence of the ratio of the total area of ​​the {111} faces on the formability becomes greater. Therefore, by satisfying the above formula, it becomes possible to exhibit even better formability.

[0030] From the same viewpoint, the upper limit of the ratio of the total area of ​​the {111} faces is not particularly limited, but it is preferable that the ratio satisfies, for example, the following formula: -1.1X+98 ≧ Percentage of the total area of ​​{111} faces (%) X = thickness of the aluminum alloy foil (μm)

[0031] Furthermore, the present invention is characterized in that the number average crystal grain size R of crystals having a face-centered cubic lattice structure obtained by performing crystal analysis by EBSD on a cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction (RD) of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil (ND) satisfies the following formula: The upper limit of the R value is, for example, about 4.5, about 4.0, or about 3.5, and the lower limit is, for example, about 1.0, about 2.0, or about 3.0. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

[0032] The aluminum alloy foil of the present invention has the above-mentioned ratio of the total area of ​​the {111} faces, and exhibits excellent formability by having such a specific relationship between the number average grain size and the thickness of the aluminum alloy foil. Conventional aluminum alloy foils do not take into consideration the relationship between the thickness of the aluminum alloy foil and the number average grain size, and there is a problem that, for example, the formability decreases when the thickness of the aluminum alloy foil is changed. In contrast, the aluminum alloy foil of the present invention has a specific relationship between the number average grain size and the thickness of the aluminum alloy foil, so that it is possible to exhibit excellent formability even when the thickness of the aluminum alloy foil is changed, and in particular, it is possible to exhibit excellent formability even when the thickness of the aluminum alloy foil is thin, as described later.

[0033] The lower limit of the number average crystal grain size R of the crystals having a face-centered cubic lattice structure is not particularly limited, but is preferably about 1 μm, and preferably satisfies, for example, the following formula: By setting the lower limit to about 1 μm or satisfying the following formula, the yield strength of the aluminum alloy foil does not become too high, and the aluminum alloy foil can be prevented from becoming too hard and decreasing its formability. 0.056X+0.4≦Number average grain size R X = thickness of the aluminum alloy foil (μm)

[0034] From the viewpoint of more effectively improving the formability of the aluminum alloy foil of the present invention, it is preferable that the standard deviation of the crystal grain size satisfies the following formula. Standard deviation of grain size St≦0.09X+0.5 X = thickness of the aluminum alloy foil (μm)

[0035] That is, since the standard deviation of the crystal grain size is small, the variation in the grain size of the crystal grains in the aluminum alloy foil is small, and the aluminum alloy foil is smoothly deformed during forming. And, as the thickness of the aluminum alloy foil becomes smaller, the influence of this standard deviation on the formability becomes greater. Therefore, by satisfying the above formula, it becomes possible to exhibit even better formability.

[0036] From the same viewpoint, the lower limit of the standard deviation of the crystal grain size is not particularly limited, but is preferably zero.

[0037] In the present invention, the ratio of the total area of ​​the {111} planes of the aluminum alloy foil, the number average grain size, and the standard deviation of the grain size can be measured by performing crystal analysis by EBSD on a cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil. A schematic diagram for explaining a method of performing crystal analysis by EBSD on a cross section of an aluminum alloy foil is shown in FIG. 12. In FIG. 12, a sample of the aluminum alloy foil 1 is placed so that Axis 1 is ND, Axis 2 is TD, and Axis 3 is RD, and an electron beam 21a is irradiated from an objective lens 21 of an SEM to a cross section 1a of the aluminum alloy foil 1, and a crystal analysis is performed from the Axis 3 direction by an EBSD detector 20. The angles formed by Axis 1, Axis 2, and Axis 3 are 90°, and the sample of the aluminum alloy foil 1 is inclined by 70° to the Axis 1 direction. That is, in a general SEM, a sample is transported horizontally and an electron beam is irradiated straight down from above, but in the present invention, the sample of aluminum alloy foil 1 is tilted 70° in the Axis 1 direction as shown in Fig. 13. The specific measurement conditions are as follows.

[0038] The number-average crystal grain size is the diameter of a circle with an area calculated by [(measurement area - area with CI value of 0.1 or less) / number of crystals]. It is calculated by combining multiple images obtained by crystal analysis using the EBSD method to obtain a diameter of approximately 10,000 μm. 2 The number average of crystals contained in the measurement area is set to 100% or more. The CI value is as described below.

[0039] In addition, the standard deviation of the grain size was calculated by removing the area with a CI value of 0.1 or less, and then combining multiple images obtained by crystal analysis using the EBSD method to obtain a standard deviation of about 10,000 μm. 2 The measurement area is This value is calculated from the distribution of crystal grain sizes (diameter when the crystal area is assumed to be a circle) of the crystals contained in the crystals.

[0040] (Measuring Equipment) A Schottky field emission scanning electron microscope equipped with an EBSD detector (manufactured by TSL Solutions Co., Ltd.) is used.

[0041] (Pretreatment) As a pretreatment, the aluminum alloy foil is cut in a direction perpendicular to the rolling direction (RD) to obtain a cross section. The rolling direction of the aluminum alloy foil is the direction in which linear rolling marks extend when the shiny surface of the aluminum alloy foil is observed with a metallurgical microscope. As a specific procedure, first, the aluminum alloy foil to be used as a sample is cut into 5 mm (perpendicular to the rolling direction) x 10 mm (rolling direction) with a trimming razor, and then embedded in resin. Next, the aluminum alloy foil is cut together with the resin using the trimming razor in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil to expose the cross section of the aluminum alloy foil. Next, the obtained cross section is trimmed using a microtome. In this trimming, in order to reduce mechanical distortion of the cut surface, the microtome is cut about 1 mm in a direction perpendicular to the cross section together with the embedded resin. Next, a broad argon beam is irradiated perpendicular to the cross section using an ion milling device to prepare a measurement cross section. This is a process for precisely exposing the cross section of the aluminum alloy foil so as to minimize mechanical damage to the crystal structure that occurred in the previous process. In the present invention, the "perpendicular direction" when cutting the aluminum alloy foil is checked under a stereomicroscope, and therefore may include an error of about 10°. That is, the permissible range for the direction perpendicular to the rolling direction is 80 to 100° to the rolling direction, and the permissible range for the direction perpendicular to the surface is 80 to 100° to the surface.

[0042] (SEM conditions) The conditions of the scanning electron microscope (SEM) used for the EBSD method are as follows: Observation magnification: 2000x (The standard observation magnification when taking photos is Polaroid 545) Acceleration voltage: 15 kV Working distance: 15mm Sample tilt angle: 70°

[0043] (EBSD conditions) The conditions for crystal analysis using the EBSD method are as follows. Step size: 200nm Analysis conditions: The following analysis is carried out using the crystal orientation analysis software OIM (Ver7.3) made by TSL Solutions Co., Ltd. Multiple images are stitched together to measure an area of ​​approximately 10,000 μm 2 The upper limit of the measurement area is, for example, about 30,000 μm 2 In this case, the measurement area is from the center to both ends in the thickness direction of the aluminum alloy foil, and the area where resin is attached to the cross section and the area where the acid-resistant film is present are excluded from the measurement area. After stitching the images, check the pole figures. If the center of the pole figure is off by 10° or more, rotate the crystal data to restore symmetry. The pole figure used as reference in this case is measured from the sample surface by XRD. When obtaining a pole figure from the surface using EBSD, the sample surface is mechanically polished, flat milled, electrolytically polished, etc., before a wide-range measurement is performed in order to remove the effects of the mechanical crystal structure of the sample surface. The pole figure obtained from the surface direction is then rotated 90° so that it is the same as the one obtained from the same orientation as the pole figure obtained from the cross section of the target sample. Use this pole figure as a reference. The analysis is performed by excluding data with a Confidence Index (CI value) of 0.1 or less, which is defined in the crystal orientation analysis software OIM (Ver. 7.3) made by TSL Solutions Co., Ltd. This makes it possible to exclude data based on the resin used in pretreatment on the front and back of the sample, grain boundaries present on the cross section, and amorphous matter. When calculating the percentage of the total area of ​​the {111} faces, the analysis is performed with a tolerance angle of 15°.

[0044] In addition, when measuring the ratio of the total area of ​​the {111} faces of the aluminum alloy foil, the number average crystal grain size, and the standard deviation of the crystal grain size for a battery using the battery packaging material of the present invention, these measurements can be performed by cutting out the battery packaging material from a flat portion of the battery.

[0045] The thickness of the aluminum alloy foil of the present invention is not particularly limited, but from the viewpoint of suitable use in battery packaging materials, it is preferably about 3 to 100 μm. As described above, the aluminum alloy foil of the present invention has the above-mentioned ratio of the total area of ​​the {111} faces, and the above-mentioned number average crystal grain size and the thickness of the aluminum alloy foil have the above-mentioned specific relationship, thereby exhibiting excellent formability. Therefore, even if the thickness of the aluminum alloy foil of the present invention is, for example, about 100 μm or less, about 80 μm or less, or even about 40 μm or less, it can exhibit excellent formability. Note that, from the viewpoint of suitable use in battery packaging materials to be subjected to molding, the thickness of the aluminum alloy foil of the present invention is preferably, for example, about 3 μm or more, about 5 μm or more, about 10 μm or more, about 15 μm or more, or about 20 μm or more. Further, the range of the thickness of the aluminum alloy foil is preferably about 3 to 100 μm, about 5 to 100 μm, about 10 to 100 μm, about 15 to 100 μm, about 20 to 100 μm, about 3 to 80 μm, about 5 to 80 μm, about 10 to 80 μm, about 15 to 80 μm, about 20 to 80 μm, about 3 to 40 μm, about 5 to 40 μm, about 15 to 40 μm, about 20 to 40 μm. Since the aluminum alloy foil of the present invention exhibits excellent formability, for example, even when the thickness of the aluminum alloy foil is very thin, such as about 10 to 40 μm or even about 10 to 20 μm, it can be suitably used as a battery packaging material.

[0046] The aluminum alloy foil of the present invention preferably contains iron from the viewpoint of improving formability. The iron content is preferably about 0.5 to 2.0 mass%, more preferably about 1.2 to 1.8 mass%. The composition of the aluminum alloy constituting the aluminum alloy foil layer can be identified by elemental analysis. The composition of the aluminum alloy can be quantified by ICP atomic emission spectroscopy (ICP-AES).

[0047] The aluminum alloy constituting the aluminum alloy foil is not particularly limited, but from the viewpoint of exhibiting excellent formability, the aluminum content in the aluminum alloy is preferably 90 mass% or more.Specific examples of the aluminum alloy preferably include soft aluminum alloys having compositions specified in JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O, etc.

[0048] The aluminum alloy foil having the above characteristics can be manufactured by a known manufacturing method, for example, by appropriately adjusting the composition of the aluminum alloy, the rolling conditions, the thickness, etc. The composition of the aluminum alloy can be, for example, adjusted by the presence or absence of a metal other than aluminum contained in the aluminum alloy (for example, at least one of iron, copper, nickel, silicon, manganese, magnesium, chromium, zinc, titanium, etc.) and the amount of the metal. The composition of the aluminum alloy is preferably the above-mentioned composition.

[0049] The rolling conditions include adjusting the rolling reduction, heating temperature, heating time, etc. For example, the method may include a process of homogenizing an aluminum metal or aluminum alloy ingot at about 500 to 600°C for about 1 to 2 hours, a hot rolling process, a cold rolling process, an intermediate annealing process in which the ingot is held at about 300 to 450°C for about 1 to 10 hours, a cold rolling process in which the rolling reduction from the intermediate annealing to the final rolling is 80% or more, more preferably 90% or more, and a final annealing process in which the ingot is held at about 250 to 400°C for about 30 to 100 hours.

[0050] In addition, it is preferable that at least one surface, preferably both surfaces, of the aluminum alloy foil 1 are chemically treated in order to stabilize adhesion and prevent dissolution and corrosion. Here, the chemical conversion treatment refers to a treatment for forming an acid-resistant film on the surface of the aluminum alloy foil. When an acid-resistant film is formed on the surface of the aluminum alloy foil, the acid-resistant film is included in the aluminum alloy foil. Examples of the chemical conversion treatment include chromate treatment using a chromium compound such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate; phosphate treatment using a phosphate compound such as sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid; and chemical conversion treatment using an aminated phenol polymer having a repeating unit represented by the following general formulas (1) to (4). Among the chromium compounds, a chromate compound is preferable. In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.

[0051] [ka]

[0052] [ka]

[0053] [ka]

[0054] [ka]

[0055] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2 Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the formulas may be the same or different. In the formulas (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the formulas (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000.

[0056] As a chemical conversion treatment method for imparting corrosion resistance to the aluminum alloy foil 1, a method is given in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate are dispersed in phosphoric acid, and then baking is performed at about 150° C. or higher to form a corrosion-resistant layer on the surface of the aluminum alloy foil 1. A resin layer in which a cationic polymer is crosslinked with a crosslinking agent may be further formed on the corrosion-resistant layer. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or a derivative thereof, and aminophenol. These cationic polymers may be used alone or in combination of two or more. Examples of the crosslinking agent include a compound having at least one functional group selected from the group consisting of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. These crosslinking agents may be used alone or in combination of two or more.

[0057] As a specific method for providing the acid-resistant film, for example, at least the inner layer surface of the aluminum alloy foil is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then a treatment liquid (aqueous solution) mainly composed of a metal phosphate such as a chromium phosphate, a titanium phosphate, a zirconium phosphate, or a zinc phosphate, or a mixture of these metal salts, or a treatment liquid (aqueous solution) mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid (aqueous solution) consisting of a mixture of these and a water-based synthetic resin such as an acrylic resin, a phenolic resin, or a urethane resin, is applied to the degreased surface by a known coating method such as a roll coating method, a gravure printing method, or a dipping method to form an acid-resistant film. For example, treatment with a chromium phosphate-based treatment solution results in an acid-resistant coating made of chromium phosphate, aluminum phosphate, aluminum oxide, aluminum hydroxide, aluminum fluoride, etc., whereas treatment with a zinc phosphate-based treatment solution results in an acid-resistant coating made of zinc phosphate hydrate, aluminum phosphate, aluminum oxide, aluminum hydroxide, aluminum fluoride, etc.

[0058] As another example of a specific method for providing an acid-resistant coating, for example, at least the inner layer surface of the aluminum alloy foil is first degreased by a well-known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is subjected to a well-known anodizing treatment to form an acid-resistant coating.

[0059] Other examples of acid-resistant coatings include phosphate-based and chromate-based coatings. Phosphate-based coatings include zinc phosphate, iron phosphate, manganese phosphate, calcium phosphate, and chromium phosphate, while chromate-based coatings include chromate chromate.

[0060] Other examples of acid-resistant coatings include those made of phosphorus compounds (e.g., phosphates), chromium compounds (e.g., chromates), fluorine compounds (fluorides), and triazine thiol compounds, which prevent delamination between the aluminum and the base layer during embossing, prevent dissolution and corrosion of the aluminum surface, particularly aluminum oxide present on the surface of the aluminum, caused by hydrogen fluoride produced by a reaction between an electrolyte and water, and improve the adhesion (wettability) of the aluminum surface, preventing delamination between the base layer and aluminum during heat sealing, and in the case of embossed types, preventing delamination between the base layer and aluminum during press molding. Among the substances that form acid-resistant coatings, an aqueous solution composed of three components, phenol resin, chromium (III) fluoride compound, and phosphoric acid, is applied to the aluminum surface, and the treatment of drying and baking is favorable.

[0061] The acid-resistant coating may include a layer having cerium oxide, phosphoric acid or a phosphate, an anionic polymer, and a crosslinking agent that crosslinks the anionic polymer, and the phosphoric acid or the phosphate may be blended in an amount of about 1 to 100 parts by mass per 100 parts by mass of the cerium oxide. It is preferable that the acid-resistant coating has a multilayer structure further including a layer having a cationic polymer and a crosslinking agent that crosslinks the cationic polymer.

[0062] Furthermore, the anionic polymer is preferably poly(meth)acrylic acid or a salt thereof, or a copolymer mainly composed of (meth)acrylic acid or a salt thereof.The crosslinking agent is preferably at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent.

[0063] The phosphoric acid or the phosphate is preferably a condensed phosphoric acid or a condensed phosphate.

[0064] The chemical conversion treatment may be performed using only one type of chemical conversion treatment, or may be performed using a combination of two or more types of chemical conversion treatments. Furthermore, these chemical conversion treatments may be performed using one type of compound alone, or may be performed using a combination of two or more types of compounds. Among the chemical conversion treatments, chromate treatment and chemical conversion treatments combining a chromium compound, a phosphoric acid compound, and an aminated phenol polymer are preferred.

[0065] Specific examples of the acid-resistant coating include those containing at least one of phosphate, chromate, fluoride, and triazine thiol. Also preferred are acid-resistant coatings containing a cerium compound. As the cerium compound, cerium oxide is preferred.

[0066] Specific examples of the acid-resistant film include a phosphate-based film, a chromate-based film, a fluoride-based film, and a triazine thiol compound film. The acid-resistant film may be one of these films, or a combination of two or more of them. Furthermore, the acid-resistant film may be formed by degreasing the chemically treated surface of the aluminum alloy foil, using a treatment liquid made of a mixture of a metal phosphate and a water-based synthetic resin, or a treatment liquid made of a mixture of a nonmetal phosphate and a water-based synthetic resin.

[0067] The composition of the acid-resistant film can be analyzed by physically peeling off the heat-sealable resin layer, adhesive layer, etc., laminated on the aluminum alloy foil in the battery packaging material, and using time-of-flight secondary ion mass spectrometry. Analysis of the composition of the acid-resistant film using time-of-flight secondary ion mass spectrometry can reveal, for example, Ce. + and Cr + A peak originating from at least one of the above is detected.

[0068] The surface of the aluminum alloy foil is preferably provided with an acid-resistant coating containing at least one element selected from the group consisting of phosphorus, chromium, and cerium. The inclusion of at least one element selected from the group consisting of phosphorus, chromium, and cerium in the acid-resistant coating on the surface of the aluminum alloy foil of the battery packaging material can be confirmed using X-ray photoelectron spectroscopy. Specifically, first, the heat-sealable resin layer, adhesive layer, etc. laminated on the aluminum alloy foil in the battery packaging material are physically peeled off. Next, the aluminum alloy foil is placed in an electric furnace and left at about 300°C for about 30 minutes to remove organic components present on the surface of the aluminum alloy foil. Then, the inclusion of these elements is confirmed using X-ray photoelectron spectroscopy of the surface of the aluminum alloy foil.

[0069] The amount of the acid-resistant film formed on the surface of the aluminum alloy foil 1 in the chemical conversion treatment is not particularly limited. For example, in the case of the above-mentioned chromate treatment, 2 It is desirable that the chromium compound is contained in an amount of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as chromium, the phosphorus compound is contained in an amount of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as phosphorus, and the aminated phenol polymer is contained in an amount of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, calculated as phosphorus, per unit area.

[0070] The thickness of the acid-resistant film is not particularly limited, but is preferably about 1 nm to 10 μm, more preferably about 1 to 100 nm, and even more preferably about 1 to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the aluminum alloy foil or the heat-fusible resin layer. The thickness of the acid-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy.

[0071] The chemical conversion treatment is carried out by applying a solution containing a compound used to form an acid-resistant film to the surface of the aluminum alloy foil by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the aluminum alloy foil so that the temperature of the aluminum alloy foil is about 70 to 200° C. In addition, before the chemical conversion treatment is carried out on the aluminum alloy foil, the aluminum alloy foil may be subjected to a degreasing treatment in advance by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, the chemical conversion treatment of the surface of the aluminum alloy foil can be carried out more efficiently.

[0072] As described below, the aluminum alloy foil of the present invention can be suitably used in the battery packaging material of the present invention. That is, the aluminum alloy foil of the present invention can be suitably used as the aluminum alloy foil in the battery packaging material composed of a laminate having at least a base layer, an aluminum alloy foil, and a heat-sealable resin layer in this order.

[0073] 2.Battery packaging materials Laminated structure As shown in Fig. 4, the battery packaging material of the present invention is composed of a laminate including at least a base material layer 2, an aluminum alloy foil 1, and a heat-sealable resin layer 3 in this order. In the battery packaging material of the present invention, the base material layer 2 is the outermost layer, and the heat-sealable resin layer 3 is the innermost layer. That is, when the battery is assembled, the heat-sealable resin layers 3 located on the periphery of the battery element are heat-sealed to each other to seal the battery element, thereby sealing the battery element.

[0074] As shown in Fig. 5, the battery packaging material of the present invention may have an adhesive layer 4 between the base material layer 2 and the aluminum alloy foil 1, if necessary, for the purpose of enhancing adhesion therebetween. Also, as shown in Fig. 6, an adhesive layer 5 may be provided between the aluminum alloy foil 1 and the heat-sealable resin layer 3, if necessary, for the purpose of enhancing adhesion therebetween. Also, as shown in Fig. 7, a surface coating layer 6 or the like may be provided on the outer side of the base material layer 2 (the side opposite to the heat-sealable resin layer 3), if necessary.

[0075] The thickness of the laminate constituting the battery packaging material of the present invention is not particularly limited, but from the viewpoint of exhibiting high moldability while making the thickness of the laminate as thin as possible, it is preferably about 160 μm or less, more preferably about 35 to 155 μm, and even more preferably about 45 to 120 μm. Even when the thickness of the laminate constituting the battery packaging material of the present invention is thin, for example, about 160 μm or less, it can exhibit excellent moldability according to the present invention. Therefore, the battery packaging material of the present invention can contribute to improving the energy density of the battery.

[0076] Layers forming the battery packaging material [Base material layer 2] In the battery packaging material of the present invention, the base layer 2 is a layer located on the outermost layer side. The material forming the base layer 2 is not particularly limited as long as it has insulating properties. Examples of materials forming the base layer 2 include resin films such as polyester resin, polyamide resin, epoxy resin, acrylic resin, fluororesin, polyurethane resin, silicone resin, phenol resin, and mixtures and copolymers thereof. Among these, polyester resin and polyamide resin are preferable, and biaxially oriented polyester resin and biaxially oriented polyamide resin are more preferable. Specific examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, copolymer polyester, polycarbonate, and the like. Specific examples of polyamide resin include nylon 6, nylon 66, a copolymer of nylon 6 and nylon 66, nylon 6,10, polyamide MXD6 (polymetaxylylene adipamide), and the like.

[0077] The base layer 2 may be formed of one layer of resin film, but may be formed of two or more layers of resin film in order to improve pinhole resistance and insulation. Specifically, a multi-layer structure in which a polyester film and a nylon film are laminated, a multi-layer structure in which multiple nylon films are laminated, a multi-layer structure in which multiple polyester films are laminated, etc. can be mentioned. When the base layer 2 has a multi-layer structure, a laminate of a biaxially oriented nylon film and a biaxially oriented polyester film, a laminate in which multiple biaxially oriented nylon films are laminated, or a laminate in which multiple biaxially oriented polyester films are laminated are preferable. For example, when the base layer 2 is formed of two layers of resin film, it is preferable to have a structure in which polyester resin and polyester resin are laminated, a structure in which polyamide resin and polyamide resin are laminated, or a structure in which polyester resin and polyamide resin are laminated, and it is more preferable to have a structure in which polyethylene terephthalate and polyethylene terephthalate are laminated, a structure in which nylon and nylon are laminated, or a structure in which polyethylene terephthalate and nylon are laminated. In addition, since polyester resin is unlikely to discolor when an electrolytic solution adheres to the surface, it is preferable to laminate the base layer 2 so that the polyester resin is located in the outermost layer in the laminated structure. When the base layer 2 has a multi-layer structure, the thickness of each layer is preferably about 2 to 25 μm.

[0078] When the base layer 2 is formed of a multi-layer resin film, two or more resin films may be laminated via an adhesive component such as an adhesive or adhesive resin, and the type and amount of the adhesive component used are the same as those of the adhesive layer 4 described below. The method for laminating two or more resin films is not particularly limited, and a known method can be adopted, such as a dry lamination method or a sandwich lamination method, and preferably a dry lamination method. When laminating by the dry lamination method, it is preferable to use a urethane adhesive as the adhesive layer. In this case, the thickness of the adhesive layer is, for example, about 2 to 5 μm.

[0079] In the present invention, from the viewpoint of improving the moldability of the battery packaging material, it is preferable that a lubricant is present on the surface of the base layer 2. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, and unsaturated fatty acid bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.

[0080] When a lubricant is present on the surface of the base layer 2, the amount of the lubricant is not particularly limited, but is preferably about 3 mg / m in an environment of a temperature of 24° C. and a relative humidity of 60%. 2 More preferably, 4 to 15 mg / m 2 about 5 to 14 mg / m 2 The degree of

[0081] A lubricant may be contained in the base layer 2. The lubricant present on the surface of the base layer 2 may be a lubricant that is exuded from the resin that constitutes the base layer 2, or a lubricant that is applied to the surface of the base layer 2.

[0082] From the viewpoint of further improving moldability, the kinetic friction coefficient of the surface on the substrate layer 2 side of the battery packaging material of the present invention is preferably about 0.5 or less, more preferably about 0.3 or less, and even more preferably about 0.2 or less. The lower limit of the kinetic friction coefficient is about 0.01. The preferred range of the kinetic friction coefficient is about 0.01 to 0.5, about 0.01 to 0.3, or about 0.01 to 0.2. The kinetic friction coefficient is a value measured in accordance with the method specified in JIS K7125:1999.

[0083] The thickness of the base layer 2 is not particularly limited as long as it functions as a base layer, but is, for example, about 3 to 50 μm, and preferably about 10 to 35 μm.

[0084] [Adhesive layer 4] In the battery packaging material of the present invention, the adhesive layer 4 is a layer that is provided between the base material layer 2 and the aluminum alloy foil 1, as necessary, in order to firmly bond them together.

[0085] The adhesive layer 4 is formed of an adhesive capable of bonding the base layer 2 and the aluminum alloy foil 1. The adhesive used to form the adhesive layer 4 may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the adhesion mechanism of the adhesive used to form the adhesive layer 4 is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, and the like.

[0086] Specific examples of adhesive components that can be used to form the adhesive layer 4 include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyester; polyether-based adhesives; polyurethane-based adhesives; epoxy-based resins; phenolic resin-based resins; polyamide-based resins such as nylon 6, nylon 66, nylon 12, and copolymerized polyamide; polyolefin-based resins such as polyolefin, carboxylic acid-modified polyolefin, and metal-modified polyolefin; polyvinyl acetate-based resins; cellulose-based adhesives; (meth)acrylic resins; polyimide-based resins; polycarbonate; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone-based resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane-based adhesives are preferred.

[0087] The adhesive layer 4 may also contain a colorant. When the adhesive layer 4 contains a colorant, the battery packaging material can be colored. As the colorant, known colorants such as pigments and dyes can be used. The colorant may be used alone or in combination of two or more types.

[0088] For example, specific examples of inorganic pigments preferably include carbon black and titanium oxide.Specific examples of organic pigments preferably include azo pigments, phthalocyanine pigments, and condensed polycyclic pigments.Examples of azo pigments include soluble pigments such as Watching Red and Carmine 6C; insoluble azo pigments such as monoazo yellow, disazo yellow, pyrazolone orange, pyrazolone red, and permanent red.Examples of phthalocyanine pigments include copper phthalocyanine pigments and metal-free phthalocyanine pigments such as blue pigments and green pigments.Examples of condensed polycyclic pigments include dioxazine violet and quinacridone violet.Examples of pigments that can be used include pearl pigments and fluorescent pigments.

[0089] Among colorants, carbon black is preferred in order to give the battery packaging material a black appearance, for example.

[0090] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.

[0091] The content of the pigment in the adhesive layer 4 is not particularly limited as long as it colors the battery packaging material, and may be, for example, about 5 to 60 mass %.

[0092] The thickness of the adhesive layer 4 is not particularly limited as long as it functions as an adhesive layer, but may be, for example, about 1 to 10 μm, and preferably about 2 to 5 μm.

[0093] [Aluminum alloy foil 1] In the battery packaging material, the aluminum alloy foil 1 is a layer that has the function of preventing water vapor, oxygen, light, and the like from penetrating into the battery, in addition to improving the strength of the battery packaging material. In the present invention, the aluminum alloy foil 1 of the present invention described above can be used as the aluminum alloy foil 1. Details of the aluminum alloy foil 1 of the present invention are as described above.

[0094] In the battery packaging material of the present invention, the aluminum alloy foil of the present invention is used, and therefore the material has excellent formability. The thickness X of the aluminum alloy foil 1 can be measured by observing the cross section of the battery packaging material even when the material is laminated in the battery packaging material. In addition, crystal analysis by EBSD method on the cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil can also be performed even when the aluminum alloy foil is laminated on the battery packaging material. The specific measurement conditions are the same as the analysis conditions for the aluminum alloy foil 1 described above, except that, as the above-mentioned (pretreatment), the battery packaging material is embedded in resin, and the battery packaging material is cut in a direction perpendicular to the rolling direction (RD) of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil (ND) to obtain a cross section of the aluminum alloy foil.

[0095] [Adhesive layer 5] In the battery packaging material of the present invention, the adhesive layer 5 is a layer that is provided between the aluminum alloy foil 1 and the heat-sealable resin layer 3, as necessary, in order to firmly bond them together.

[0096] The adhesive layer 5 is formed by a resin capable of bonding the aluminum alloy foil 1 and the heat-sealable resin layer 3. The adhesive mechanism, the type of adhesive component, and the like of the resin used to form the adhesive layer 5 can be the same as those of the adhesive layer 4. In addition, the resin used to form the adhesive layer 5 can be a polyolefin-based resin such as polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, and carboxylic acid-modified cyclic polyolefin exemplified in the heat-sealable resin layer 3 described later. From the viewpoint of excellent adhesion between the aluminum alloy foil 1 and the heat-sealable resin layer 3, carboxylic acid-modified polyolefin is preferable as the polyolefin, and carboxylic acid-modified polypropylene is particularly preferable. That is, the resin constituting the adhesive layer 5 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The resin constituting the adhesive layer 5 can be analyzed by, for example, infrared spectroscopy, gas chromatography mass spectrometry, and the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, it is found that the maleic anhydride-modified polyolefin has a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected nearby.

[0097] Furthermore, from the viewpoint of obtaining a battery packaging material having good adhesiveness while reducing the thickness of the battery packaging material, the adhesive layer 5 may be a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. Preferred examples of the acid-modified polyolefin include the same carboxylic acid-modified polyolefins and carboxylic acid-modified cyclic polyolefins as those exemplified for the heat-sealable resin layer 3.

[0098] The curing agent is not particularly limited as long as it can cure the acid-modified polyolefin, and examples of the curing agent include epoxy-based curing agents, polyfunctional isocyanate-based curing agents, carbodiimide-based curing agents, and oxazoline-based curing agents.

[0099] The epoxy curing agent is not particularly limited as long as it is a compound having at least one epoxy group. Examples of the epoxy curing agent include epoxy resins such as bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, and polyglycerin polyglycidyl ether.

[0100] The polyfunctional isocyanate curing agent is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of the polyfunctional isocyanate curing agent include isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers.

[0101] The carbodiimide-based curing agent is not particularly limited as long as it is a compound having at least one carbodiimide group (-N=C=N-). As the carbodiimide-based curing agent, a polycarbodiimide compound having at least two carbodiimide groups is preferable.

[0102] The oxazoline-based curing agent is not particularly limited as long as it is a compound having an oxazoline skeleton, and specific examples of the oxazoline-based curing agent include the EPOCROS series manufactured by Nippon Shokubai Co., Ltd.

[0103] From the viewpoint of improving the adhesion between the aluminum alloy foil 1 and the heat-fusible resin layer 3 through the adhesive layer 5, the curing agent may be composed of two or more types of compounds.

[0104] The content of the curing agent in the resin composition forming the adhesive layer 5 is preferably in the range of approximately 0.1 to 50 mass%, more preferably in the range of approximately 0.1 to 30 mass%, and even more preferably in the range of approximately 0.1 to 10 mass%.

[0105] The thickness of the adhesive layer 5 is not particularly limited as long as it functions as an adhesive layer, but when an adhesive exemplified in the adhesive layer 4 is used, the thickness is preferably about 2 to 10 μm, more preferably about 2 to 5 μm. When a resin exemplified in the heat-fusible resin layer 3 is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. When a cured product of an acid-modified polyolefin and a curing agent is used, the thickness is preferably about 30 μm or less, more preferably about 0.1 to 20 μm, and even more preferably about 0.5 to 5 μm. When the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed by applying the resin composition and curing it by heating or the like.

[0106] [Thermal adhesive resin layer 3] In the battery packaging material of the present invention, the heat-sealable resin layer 3 corresponds to the innermost layer, and is a layer that seals the battery element by being heat-sealed to each other when the battery is assembled.

[0107] The resin component used in the heat-sealable resin layer 3 of the present invention is not particularly limited as long as it is heat-sealable, and examples thereof include polyolefins and acid-modified polyolefins. That is, the resin constituting the heat-sealable resin layer 3 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The inclusion of a polyolefin skeleton in the resin constituting the heat-sealable resin layer 3 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, it is found that the maleic anhydride-modified polyolefin has a wavelength of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0108] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); and ethylene-butene-propylene terpolymers. Among these polyolefins, preferred are polyethylene and polypropylene, and more preferred is polypropylene.

[0109] The polyolefin may be a cyclic polyolefin. The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Styrene is also included as a constituent monomer. Among these, cyclic alkenes are preferred, and norbornene is more preferred.

[0110] The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of the above-mentioned polyolefin with a carboxylic acid, etc. Examples of the carboxylic acid used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0111] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin by replacing it with an α,β-unsaturated carboxylic acid or its anhydride, or by block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or its anhydride to the cyclic polyolefin. The cyclic polyolefin to be acid-modified is the same as described above. The carboxylic acid used for the modification is the same as that used for the modification of the acid-modified cycloolefin copolymer.

[0112] Among these resin components, polyolefins are preferred; propylene copolymers are more preferred. Examples of propylene copolymers include copolymers of propylene and other olefins, such as ethylene-propylene copolymer, propylene-butene copolymer, and ethylene-propylene-butene copolymer. The ratio of propylene units contained in polypropylene is preferably about 50 to 100 mol%, more preferably about 80 to 100 mol%, from the viewpoint of further improving the insulating properties and durability of the battery packaging material. The ratio of ethylene units contained in polyethylene is preferably about 50 to 100 mol%, more preferably about 80 to 100 mol%, from the viewpoint of further improving the insulating properties and durability of the battery packaging material. The ethylene copolymer and propylene copolymer may each be either a random copolymer or a block copolymer, and a random propylene copolymer is preferred.

[0113] The heat-sealable resin layer 3 of the present invention preferably contains polypropylene, and preferably contains a layer formed of polypropylene. The heat-sealable resin layer 3 may be formed of one type of resin component alone, or may be formed of a blend polymer of two or more types of resin components. Furthermore, the heat-sealable resin layer 3 may be formed of only one layer, or may be formed of two or more layers of the same or different resin components.

[0114] In the present invention, from the viewpoint of improving the moldability of the battery packaging material, it is preferable that a lubricant is present on the surface of the heat-sealable resin layer 3. The lubricant is not particularly limited, and a known lubricant can be used, for example, those exemplified for the base material layer 2 above. The lubricant may be used alone or in combination of two or more. The amount of lubricant present on the surface of the heat-sealable resin layer 3 is not particularly limited, and from the viewpoint of improving the moldability of the battery packaging material, it is preferably 10 to 50 mg / m in an environment at a temperature of 24° C. and a relative humidity of 60%. 2 about 15 to 40 mg / m 2 The degree of

[0115] A lubricant may be contained in the thermally adhesive resin layer 3. The lubricant present on the surface of the thermally adhesive resin layer 3 may be a lubricant exuded from the resin constituting the thermally adhesive resin layer 3, or a lubricant applied to the surface of the thermally adhesive resin layer 3.

[0116] From the viewpoint of further improving moldability, the dynamic friction coefficient of the surface of the heat-sealable resin layer 3 of the battery packaging material of the present invention is preferably about 0.5 or less, more preferably about 0.3 or less, and even more preferably about 0.2 or less. The lower limit of the dynamic friction coefficient is about 0.01. The preferred range of the dynamic friction coefficient is about 0.01 to 0.5, about 0.01 to 0.3, or about 0.01 to 0.2. The dynamic friction coefficient is a value measured in accordance with the method specified in JIS K7125:1999.

[0117] The thickness of the heat-sealable resin layer 3 of the present invention is not particularly limited as long as it functions as a heat-sealable resin layer, but from the viewpoint of improving moldability, the thickness is, for example, about 10 to 40 μm, preferably about 15 to 40 μm.

[0118] [Surface coating layer 6] In the battery packaging material of the present invention, a surface coating layer 6 may be provided on the substrate layer 2 (the side of the substrate layer 2 opposite to the aluminum alloy foil 1) as needed for the purpose of improving design, electrolyte resistance, abrasion resistance, formability, etc. The surface coating layer 6 is a layer located on the outermost layer when the battery is assembled.

[0119] The surface coating layer 6 can be formed from, for example, polyvinylidene chloride, polyester resin, urethane resin, acrylic resin, epoxy resin, etc. Among these, the surface coating layer 6 is preferably formed from a two-component curing resin. Examples of the two-component curing resin forming the surface coating layer 6 include a two-component curing urethane resin, a two-component curing polyester resin, and a two-component curing epoxy resin. The surface coating layer 6 may also contain an additive.

[0120] Examples of additives include fine particles having a particle size of about 0.5 nm to 5 μm. The material of the additive is not particularly limited, and examples thereof include metals, metal oxides, inorganic substances, and organic substances. The shape of the additive is also not particularly limited, and examples thereof include spherical, fibrous, plate-like, amorphous, and balloon-like. Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, montmorillonite, synthetic mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, and nickel. These additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoints of dispersion stability, cost, etc. Furthermore, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.

[0121] The method for forming the surface coating layer 6 is not particularly limited, and may be, for example, a method for applying a two-component curing resin that forms the surface coating layer 6 to one surface of the base material layer 2. When an additive is added, the additive may be added to the two-component curing resin, mixed, and then applied.

[0122] The content of the additive in the surface coating layer 6 is not particularly limited, but is preferably about 0.05 to 1.0 mass %, and more preferably about 0.1 to 0.5 mass %.

[0123] The thickness of the surface coating layer 6 is not particularly limited as long as the surface coating layer 6 exhibits the above-mentioned functions, and is, for example, about 0.5 to 10 μm, preferably about 1 to 5 μm.

[0124] 3. Manufacturing method of battery packaging material The manufacturing method of the battery packaging material of the present invention is not particularly limited as long as a laminate is obtained in which layers of a predetermined composition are laminated, and the method includes at least a lamination step of obtaining a laminate having a base layer, an aluminum alloy foil, and a heat-sealable resin layer in this order, and a method using the aluminum alloy foil of the present invention as the aluminum alloy foil can be adopted.

[0125] An example of a method for producing the battery packaging material of the present invention is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") having a base layer 2, an adhesive layer 4, and an aluminum alloy foil 1 in this order is formed. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used for forming the adhesive layer 4 is applied to the base layer 2 or the aluminum alloy foil 1, the surface of which has been chemically treated as necessary, by a coating method such as extrusion, gravure coating, or roll coating, and then dried, and the aluminum alloy foil 1 or the base layer 2 is laminated thereon, and the adhesive layer 4 is cured.

[0126] Next, the adhesive layer 5 and the heat-fusible resin layer 3 are laminated in this order on the aluminum alloy foil 1 of the laminate A. For example, there may be mentioned (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 3 on the aluminum alloy foil 1 of the laminate A by co-extruding them (co-extrusion lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 3 are laminated, and laminating this on the aluminum alloy foil 1 of the laminate A by a thermal lamination method, (3) a method of laminating an adhesive for forming the adhesive layer 5 on the aluminum alloy foil 1 of the laminate A by an extrusion method or a solution coating, drying at a high temperature, and baking, and laminating a heat-sealable resin layer 3 previously formed into a sheet-like film on this adhesive layer 5 by a thermal lamination method, and (4) a method of laminating the laminate A and the heat-sealable resin layer 3 via the adhesive layer 5 while pouring a molten adhesive layer 5 between the aluminum alloy foil 1 of the laminate A and the heat-sealable resin layer 3 previously formed into a sheet-like film (sandwich lamination method), and the like.

[0127] When a surface coating layer is provided, the surface coating layer is laminated on the surface of the base layer 2 opposite to the aluminum alloy foil 1. The surface coating layer can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer to the surface of the base layer 2. The order of the step of laminating the aluminum alloy foil 1 on the surface of the base layer 2 and the step of laminating the surface coating layer on the surface of the base layer 2 is not particularly limited. For example, after forming the surface coating layer on the surface of the base layer 2, the aluminum alloy foil 1 may be formed on the surface of the base layer 2 opposite to the surface coating layer.

[0128] The method for causing a lubricant to be present on the surface of the base layer 2 or the heat-sealable resin layer 3 is not particularly limited, and examples thereof include a method in which a lubricant is blended into the resin constituting the base layer 2 or the heat-sealable resin layer 3 and the lubricant is allowed to seep onto the surface as necessary, and a method in which a lubricant is applied to the surface of the base layer 2 or the heat-sealable resin layer 3.

[0129] As described above, a laminate is formed which includes, in this order, the surface coating layer 6 which is provided as required, the base layer 2, the adhesive layer 4 which is provided as required, the aluminum alloy foil 1 which has been subjected to a chemical conversion treatment on the surface as required, the adhesive layer 5, and the heat-fusible resin layer 3. In order to strengthen the adhesiveness of the adhesive layer 4 and the adhesive layer 5 which is provided as required, the laminate may be subjected to a heat treatment such as a hot roll contact type, a hot air type, a near infrared type, or a far infrared type. Conditions for such a heat treatment include, for example, about 150 to 250° C. for about 1 to 5 minutes.

[0130] In the battery packaging material of the present invention, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, in order to improve or stabilize the film-forming properties, lamination processing, suitability for secondary processing of the final product (pouching, embossing), etc.

[0131] 4. Applications of battery packaging materials The battery packaging material of the present invention is used as a packaging material for hermetically housing battery elements such as a positive electrode, a negative electrode, and an electrolyte.

[0132] Specifically, a battery element including at least a positive electrode, a negative electrode, and an electrolyte is covered with the battery packaging material of the present invention in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the battery element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to provide a battery using the battery packaging material. When a battery element is housed using the battery packaging material of the present invention, the battery packaging material is used so that the heat-sealable resin portion of the battery packaging material of the present invention faces inside (the surface in contact with the battery element).

[0133] The battery packaging material of the present invention may be used for either primary or secondary batteries, but is preferably used for secondary batteries. The type of secondary battery to which the battery packaging material of the present invention is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries are suitable applications of the battery packaging material of the present invention. EXAMPLES

[0134] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the examples.

[0135] Examples 1 to 7 and Comparative Examples 1 to 4 A biaxially oriented nylon film (thickness: 25 μm) was used as the resin film constituting the base layer. One side of the biaxially oriented nylon film was subjected to a corona treatment. Erucic acid amide was applied as a lubricant to the side of the biaxially oriented nylon film that was not subjected to the corona treatment (application amount: 10 mg / m 2 On the other hand, biaxially oriented nylon film was subjected to corona treatment. An adhesive layer consisting of a two-liquid urethane adhesive with a polyester polyol-based base agent and an aromatic isocyanate-based curing agent was applied to the surface of the aluminum alloy foil so that the thickness after curing would be 3 μm. Next, each aluminum alloy foil having the properties shown in Table 1 was prepared, and the adhesive layer side of the base layer and the chemically treated surface of the aluminum alloy foil were laminated together, pressed and heated to adhere, and then aging treatment was performed to produce a laminate in which a biaxially oriented nylon film / adhesive layer / aluminum alloy foil were laminated in this order. The chemical conversion treatment of the aluminum alloy foil was performed using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m2. 2 (dry weight) was applied to both sides of the aluminum alloy foil by roll coating, and then baked. The aluminum alloy foils of Examples 1 to 7 and Comparative Examples 1 to 4 were manufactured by the above-mentioned known method by adjusting the composition, rolling conditions, etc., and had different properties shown in Table 1, such as number average crystal grain size.

[0136] Separately, an acid-modified polypropylene resin (unsaturated carboxylic acid graft-modified random polypropylene graft-modified with unsaturated carboxylic acid) constituting the adhesive layer and a polypropylene (random copolymer) constituting the heat-sealable resin layer were co-extruded to produce a two-layer co-extruded film consisting of an adhesive layer having a thickness of 20 μm and a heat-sealable resin layer having a thickness of 20 μm. Next, the two-layer co-extruded film produced above was laminated so that the adhesive layer of the two-layer co-extruded film produced above was in contact with the aluminum alloy foil side of the laminate consisting of the biaxially oriented nylon film / adhesive layer / aluminum alloy foil, and heated to obtain a laminate in which the base layer (biaxially oriented nylon film) / adhesive layer / aluminum alloy foil / adhesive layer / heat-sealable resin layer were laminated in this order. The obtained laminate was once cooled and then subjected to heat treatment to obtain each battery packaging material.

[0137] <Measurements of the total area ratio of {111} faces, number average grain size, and standard deviation of grain size> A cross section perpendicular to the rolling direction of each of the aluminum alloy foils used above was subjected to crystal analysis by the EBSD method, and the ratio of the total area of ​​the {111} planes of the aluminum alloy foils, the number average crystal grain size, and the standard deviation of the crystal grain size were measured. The details of the measurement conditions are as follows. The measurement results are shown in Table 1. When the maximum crystal grain size was measured for reference when measuring the number average crystal grain size, the maximum crystal grain size of the aluminum alloy foil of Example 1 was 8.6 μm, and the maximum crystal grain size of the aluminum alloy foil of Comparative Example 3 was 12.5 μm. The number average crystal grain size is the diameter when the area calculated by [(measurement area-area with CI value of 0.1 or less) / number of crystals] is assumed to be a circle, and a circle of about 10,000 μm was obtained by connecting multiple images obtained by crystal analysis by the EBSD method. 2 The maximum crystal grain size is the number-average crystal grain size of the crystals contained in the measurement area, which is equal to or larger than the CI value of 0.1. The maximum crystal grain size is the value measured for the largest crystal among the crystals contained in the measurement area, assuming that the crystal shape is circular. The standard deviation of the crystal grain size is approximately 10,000 μm, which is calculated by combining multiple images obtained by crystal analysis using the EBSD method after removing the area with a CI value of 0.1 or less. 2 The crystal grain size was calculated from the distribution of the crystal grain size (diameter when the crystal area is assumed to be a circle) of the crystals contained in the above measurement area.

[0138] (Measuring Equipment) A Schottky field emission scanning electron microscope equipped with an EBSD detector (manufactured by TSL Solutions Co., Ltd.) is used.

[0139] (Pretreatment) As a pretreatment, the aluminum alloy foil is cut in a direction perpendicular to the rolling direction (RD) to obtain a cross section. The rolling direction of the aluminum alloy foil is the direction in which linear rolling marks extend when the shiny surface of the aluminum alloy foil is observed with a metallurgical microscope. As a specific procedure, the aluminum alloy foil to be used as a sample is cut into 5 mm (perpendicular to the rolling direction) x 10 mm (rolling direction) with a trimming razor, and then embedded in resin. Next, the aluminum alloy foil is cut together with the resin using the trimming razor in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil, to expose the cross section of the aluminum alloy foil. Next, the obtained cross section is trimmed using a microtome (ultramicrotome manufactured by Leica Microsystems). In this trimming, in order to reduce mechanical distortion of the cross section shape, the microtome is cut about 1 mm in a direction perpendicular to the cross section together with the embedded resin. Next, a broad argon beam was irradiated perpendicularly to the cross section using an ion milling device (Hitachi High-Technologies Corporation) under conditions of a protrusion width of 50 μm, a voltage of 6 kV, and 4 hours to prepare a cross section for measurement. This is a process to precisely expose the cross section of the aluminum alloy foil so as to minimize mechanical damage to the crystal structure that occurred in the previous process.

[0140] (SEM conditions) The conditions of the scanning electron microscope (SEM) used for the EBSD method are as follows: Observation magnification: 2000x (The standard observation magnification when taking photos is Polaroid 545) Acceleration voltage: 15 kV Working distance: 15mm Sample tilt angle: 70°

[0141] (EBSD conditions) The conditions for crystal analysis using the EBSD method are as follows. Step size: 200nm Analysis conditions: The following analyses were carried out using the crystal orientation analysis software OIM (Ver. 7.3) made by TSL Solutions Co., Ltd. Multiple images are stitched together to measure an area of ​​approximately 10,000 μm 2 At this time, the measurement area was from the center to both ends in the thickness direction of the aluminum alloy foil, and the area where the resin was attached to the cross section and the area where the acid-resistant film was present were excluded from the measurement area. After stitching the images together, the pole figures were checked. The analysis was performed excluding data with a Confidence Index (CI value) of 0.1 or less, which is defined by the crystal orientation analysis software OIM manufactured by TSL Solutions Co., Ltd. When calculating the percentage of the total area of ​​the {111} faces, the analysis was performed with a tolerance angle of 15°.

[0142] A graph showing the relationship between the thickness X (μm) of the aluminum alloy foils of Examples 1 to 7 and Comparative Examples 1 to 4 and the ratio (%) of the total area of ​​the {111} faces is shown in Fig. 8. A reference line of the ratio (%) of the total area of ​​the {111} faces = -1.1X + 66 is drawn in Fig. 8. In Fig. 8 to Fig. 11, ◯ indicates the results of the Examples and △ indicates the results of the Comparative Examples.

[0143] 9 is a graph showing the relationship between the thickness X (μm) and the number average grain size R (μm) of the aluminum alloy foils of Examples 1 to 7 and Comparative Examples 1 to 4. In Fig. 9, a reference line of number average grain size R = 0.056X + 2.0 is drawn.

[0144] A graph showing the relationship between the thickness X (μm) of the aluminum alloy foils of Examples 1 to 7 and Comparative Examples 1 to 4 and the standard deviation of the crystal grain size is shown in Fig. 10. A reference line of the standard deviation St of the crystal grain size = 0.09X + 0.5 is drawn in Fig. 10.

[0145] <Measurement of limit forming depth> Each battery packaging material obtained above was cut into strips of 150 mm (TD) x 100 mm (MD), and 10 test samples were prepared for each battery packaging material. The MD of the battery packaging material corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the battery packaging material corresponds to the TD of the aluminum alloy foil. The same plane perpendicular to the MD and RD is the TD. The rolling direction of the aluminum alloy foil can be confirmed by the rolling marks on the aluminum alloy foil. The mold used was a straight mold consisting of a rectangular male mold of 30 mm (MD) x 50 mm (TD) and a female mold with a clearance of 0.5 mm from the male mold. The test sample was placed on the female mold so that the heat-sealable resin layer side was located on the male mold side. For each of the 10 test samples of the battery packaging material, the test sample was pressed with a surface pressure of 0.1 MPa to a predetermined molding depth, and cold formed (drawn one-stage forming). The test samples after cold forming were lit by a penlight in a dark room to check whether pinholes or cracks had occurred in the aluminum alloy foil by light transmission. The deepest forming depth at which no pinholes or cracks occurred in the aluminum alloy foil among all 10 test samples was defined as A mm, and the number of test samples at which pinholes or other defects occurred in the aluminum alloy foil at the shallowest forming depth was defined as B. The value calculated by the following formula was defined as the limit forming depth of the battery packaging material. The results are shown in Table 1. Limit forming depth = A mm + (0.5 mm / 10 pieces) x (10 pieces - B pieces)

[0146] <Evaluation of moldability> The relationship between the limit forming depth and the aluminum alloy foil thickness X (μm) of each battery packaging material in Examples 1 to 7 and Comparative Examples 1 to 4 is plotted in the graph of Fig. 11. Since the limit forming depth varies depending on the thickness of the aluminum alloy foil, the following two criteria were set for the forming depth in order to evaluate formability independent of thickness. The reference line for the following criterion 2 is shown in Fig. 11. Criterion 1: Forming depth (mm) = Aluminum alloy foil thickness X (μm) × 0.14 + 2 Criterion 2: Forming depth (mm) = Aluminum alloy foil thickness X (μm) × 0.12 + 2 Based on these criteria 1 and 2, the moldability of each of the battery packaging materials in Examples 1 to 7 and Comparative Examples 1 to 4 was evaluated according to the following criteria. The results are shown in Table 1. a: Limit forming depth (mm) ≧ Aluminum alloy foil thickness X (μm) × 0.14 + 2 b: Aluminum alloy foil thickness X (μm) × 0.14 + 2 > Limit forming depth (mm) ≥ Aluminum alloy foil thickness X (μm) × 0.12 + 2 c: Aluminum alloy foil thickness X (μm) × 0.12 + 2 > limit forming depth (mm)

[0147] [Table 1]

[0148] From the results shown in Table 1, it can be seen that the battery packaging materials using the aluminum alloy foils of Examples 1 to 7, in which the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure obtained by performing crystal analysis by EBSD on a cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil, is 10% or more, and the number average crystal grain size R of the crystals of the face-centered cubic lattice structure obtained by performing crystal analysis by EBSD on the cross section satisfies the condition of "number average crystal grain size R≦0.056X+2.0", are all excellent in formability. On the other hand, the battery packaging materials of Comparative Examples 1 to 4, in which the ratio of the total area of ​​the {111} faces was 10% or more but the number average crystal grain size R did not satisfy the condition of "number average crystal grain size R≦0.056X+2.0", all had inferior moldability compared to the Examples. [Explanation of symbols]

[0149] 1...Aluminum alloy foil 1a...Cross section 2...Base material layer 3…Thermofusible resin layer 4...Adhesive layer 5…Adhesion layer 6…Surface coating 10…Battery packaging materials T…pressure extension mark

Claims

1. The laminate is made up of at least a surface coating layer, a base layer, an aluminum alloy foil, and a heat-sealable resin layer, in this order; The surface coating layer contains titanium oxide, A cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is subjected to crystal analysis by an EBSD method, and the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure is 10% or more; and The cross section is subjected to crystal analysis by an EBSD method, and the number average crystal grain size R (μm) of crystals having a face-centered cubic lattice structure obtained by the cross section satisfies the following formula. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

2. The laminate is made up of at least a surface coating layer, a base layer, an aluminum alloy foil, and a heat-sealable resin layer, in this order; The surface coating layer contains kaolin, A cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is subjected to crystal analysis by an EBSD method, and the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure is 10% or more; and The cross section is subjected to crystal analysis by an EBSD method, and the number average crystal grain size R (μm) of crystals having a face-centered cubic lattice structure obtained by the cross section satisfies the following formula. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

3. The laminate is made up of at least a surface coating layer, a base layer, an aluminum alloy foil, and a heat-sealable resin layer, in this order; The surface coating layer contains silica, A cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is subjected to crystal analysis by an EBSD method, and the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure is 10% or more; and The cross section is subjected to crystal analysis by an EBSD method, and the number average crystal grain size R (μm) of crystals having a face-centered cubic lattice structure obtained by the cross section satisfies the following formula. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

4. The laminate is made up of at least a surface coating layer, a base layer, an aluminum alloy foil, and a heat-sealable resin layer, in this order; the surface coating layer comprises at least two selected from the group consisting of talc, silica, graphite, kaolin, montmorillonite, synthetic mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, and nickel; A cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is subjected to crystal analysis by an EBSD method, and the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure is 10% or more; and The cross section is subjected to crystal analysis by an EBSD method, and the number average crystal grain size R (μm) of crystals having a face-centered cubic lattice structure obtained by the cross section satisfies the following formula. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

5. The laminate is composed of at least a base layer, an aluminum alloy foil, an adhesive layer, and a heat-sealable resin layer, in this order; the adhesive layer is formed of a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, A cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is subjected to crystal analysis by an EBSD method, and the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure is 10% or more; and The cross section is subjected to crystal analysis by an EBSD method, and the number average crystal grain size R (μm) of crystals having a face-centered cubic lattice structure obtained by the cross section satisfies the following formula. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

6. The laminate is composed of at least a base layer, an aluminum alloy foil, an adhesive layer, and a heat-sealable resin layer, in this order; the adhesive layer is formed of a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the cured product is at least one selected from the group consisting of an epoxy-based curing agent, a polyfunctional isocyanate-based curing agent, a carbodiimide-based curing agent, and an oxazoline-based curing agent; A cross section obtained by cutting the aluminum alloy foil in a direction perpendicular to the rolling direction of the aluminum alloy foil and perpendicular to the surface of the aluminum alloy foil is subjected to crystal analysis by an EBSD method, and the ratio of the total area of ​​{111} faces to the total area of ​​crystal faces of a face-centered cubic lattice structure is 10% or more; and The cross section is subjected to crystal analysis by an EBSD method, and the number average crystal grain size R (μm) of crystals having a face-centered cubic lattice structure obtained by the cross section satisfies the following formula. Number average grain size R≦0.056X+2.0 X = thickness of the aluminum alloy foil (μm)

7. The battery packaging material according to any one of claims 1 to 6, wherein the ratio (%) of the total area of ​​the {111} faces to the total area of ​​the crystal faces of the face-centered cubic lattice structure satisfies the following formula: The ratio (%) of the total area of ​​{111} faces to the total area of ​​the crystal faces of the face-centered cubic lattice structure is ≧−1.1X+66 X = thickness of the aluminum alloy foil (μm)

8. The battery packaging material according to any one of claims 1 to 7, wherein the standard deviation St of the crystal grain size satisfies the following formula: Standard deviation of grain size St≦0.09X+0.5 X = thickness of the aluminum alloy foil (μm)

9. The battery packaging material according to any one of claims 1 to 8, which contains iron.

10. The battery packaging material according to any one of claims 1 to 9, wherein the surface of the aluminum alloy foil is provided with an acid-resistant coating containing at least one element selected from the group consisting of phosphorus, chromium, and cerium.

11. The aluminum alloy foil has an acid-resistant coating on a surface thereof, When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, Ce + and Cr + The battery packaging material according to any one of claims 1 to 9, wherein a peak derived from at least one of the following is detected.

12. The battery packaging material according to any one of claims 1 to 9, wherein the surface of the aluminum alloy foil is provided with an acid-resistant coating containing at least one selected from the group consisting of a phosphorus compound salt, a chromium compound, a fluorine compound, and a triazine thiol compound.

13. The battery packaging material according to any one of claims 1 to 9, wherein a surface of the aluminum alloy foil is provided with an acid-resistant coating containing a cerium compound.

14. A battery, comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the battery packaging material according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Aluminum alloy foil for lithium battery outer packaging and its manufacturing method

    JP2014065956A

  • Exterior material for power storage device

    JP2014078513A

  • Sheath material for lithium ion battery

    JP2014130845A

  • Aluminum alloy soft foil and manufacturing method thereof

    JP2015203154A

  • Aluminum alloy foil excellent in elongation property and method for producing aluminum foil

    JP2016156059A